Analisis Hukum Islam terhadap Praktik Jual Beli Online yang Melanggar UUPK : Studi Kasus pada Mahasiswa PPKn UNIMED sebagai Konsumen - Aina Mulia Rizky; Amalia Apriliani; Devi Syalwa Syahfitri; Joya Urmila Lubis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of digital technology has fueled the rise of online buying and selling practices through marketplaces and social media, including among students. This convenience is not without legal and ethical issues, such as misdescribed goods, fraud, and the weakening of consumers' position compared to businesses. This research uses a normative method with a qualitative approach through literature review, regulatory analysis, and interviews with UNIMED Civics students to examine consumer protection from the perspective of positive law and Islamic law. Theoretical studies indicate that Law Number 8 of 1999 concerning Consumer Protection (UUPK) affirms consumers' rights to security, comfort, accurate information, and opens up opportunities, although its implementation remains hampered by low legal awareness. Meanwhile, muamalah jurisprudence affirms the validity of a sale and purchase contract if it meets the pillars and conditions, and upholds the values ​​of honesty (ṣidq), justice (‘adl), trustworthiness, and the prohibition of gharar and tadlis. The results of the study indicate that violations of online transactions not only violate the UUPK but also undermine Islamic business ethics. Therefore, the integration of Islamic law and positive law is necessary to strengthen digital consumer protection in a fair and beneficial manner.